Water mites of the family Torrenticolidae (Acari: Hydrachnidia) from Thailand, Part II. The genus Monatractides K.Viets - Pesic, Vladimir; Smit, Harry (Zootaxa, 2009)
New records of water mites of the genus Monatractides K.Viets (Acari: Hydrachnidia, Torrenticolidae) from streams in Thailand are presented. One species, Monatractides gledhilli, new to science is described; a first description of the male is given for M. circuloides (Halík); first records from Thailand are given for Monatractides neoapratima (Wiles), M. circuloides (Halík), M. kyphophorus (K. Viets), M. parviventris (K. Viets), M. longiventris (K. Viets), M. oxystomus (K. Viets), M. cf. garhwaliensis Pesic et al., M. cf. tuzovskyi Pesic et al., M. macroporus K. Viets-complex and M. plumosa (Wiles). The zoogeographical characteristics of the Thailands torrenticolids are outlined. Additional work is highly desirable to clarify the taxonomy of SE Asian Monatractides species.